Damaging variants in FOXI3 cause microtia and craniofacial microsomia - Quiat, Daniel (2023)
Purpose: Craniofacial microsomia (CFM) represents a spectrum of craniofacial malformations, ranging from isolated microtia with or without aural atresia to underdevelopment of the mandible, maxilla, orbit, facial soft tissue, and/or facial nerve. The genetic causes of CFM remain largely unknown. Methods: We performed genome sequencing and linkage analysis in patients and families with microtia and CFM of unknown genetic etiology. The functional consequences of damaging missense variants were evaluated through expression of wild-type and mutant proteins in vitro. Results: We studied a 5-generation kindred with microtia, identifying a missense variant in FOXI3 (p.Arg236Trp) as the cause of disease (logarithm of the odds = 3.33). We subsequently identified 6 individuals from 3 additional kindreds with microtia-CFM spectrum phenotypes harboring damaging variants in FOXI3, a regulator of ectodermal and neural crest development. Missense variants in the nuclear localization sequence were identified in cases with isolated microtia with aural atresia and found to affect subcellular localization of FOXI3. Loss of function variants were found in patients with microtia and mandibular hypoplasia (CFM), suggesting dosage sensitivity of FOXI3. Conclusion: Damaging variants in FOXI3 are the second most frequent genetic cause of CFM, causing 1% of all cases, including 13% of familial cases in our cohort.